Kritik der objektiven Zurechnung - Leu, Nicolas (sui generis Verlag, 2022)
In German literature, the doctrine of objective attribution has long since established itself as the prevailing opinion. In Switzerland, it has found its way into the literature and has already been included in the case law of the Federal Supreme Court on negligence offences. However, critical voices point out that the current status of the discussion is characterized by a large number of different approaches, some of which differ only marginally. A look at the literature actually shows that many essential questions, such as the raison d'être of individual aspects of attribution, are still disputed today. In this dissertation, Nicolas Leu therefore subjects objective attribution to a comprehensive and critical review that also takes into account the criminal offense system in which objective attribution is embedded.